The Influence of Broken Home Conditions on Sustained Attention and Cognitive Load in Literacy and Numeracy Learning: A Systematic Literature Review and Bibliometric Analysis - Leli Astuni; Ellianawati Ellianawati; Bambang Subali (JURNAL ASIMILASI PENDIDIKAN, 2026)
Abstract :Family conditions have a significant influence on students' psychological and academic development. One family condition often associated with student learning problems is broken homes. This study aims to examine the effect of broken homes on sustained attention and cognitive load in literacy and numeracy learning through a literature review approach. The research method uses a literature study by collecting national and international scientific articles through Google Scholar, Scopus, and Crossref databases using the Publish or Perish application and visualization analysis using VOSviewer. The analysis technique is carried out through the stages of identification, screening, eligibility, and inclusion based on the PRISMA diagram. The results of the study indicate that broken homes have an impact on decreasing students' attention focus, increasing emotional stress, and high cognitive load during the literacy and numeracy learning process. In addition, students tend to experience difficulty in maintaining sustained attention due to psychological stress originating from the family environment. This study demonstrates the importance of emotional support, adaptive learning strategies, and a humanistic approach from teachers to help students with broken homes. abstrak: Bermain Kondisi keluarga memiliki pengaruh yang besar terhadap perkembangan psikologis dan akademik peserta didik. Salah satu kondisi keluarga yang sering dikaitkan dengan permasalahan belajar siswa adalah broken home. Penelitian ini bertujuan untuk mengkaji pengaruh kondisi broken home terhadap sustained attention dan beban kognitif dalam pembelajaran literasi dan numerasi melalui pendekatan literature review. Metode penelitian menggunakan studi kepustakaan dengan mengumpulkan artikel ilmiah nasional dan internasional melalui database Google Scholar, Scopus, dan Crossref menggunakan bantuan aplikasi Publish or Perish serta analisis visualisasi menggunakan VOSviewer. Teknik analisis dilakukan melalui tahapan identifikasi, screening, eligibility, dan inclusion berdasarkan diagram PRISMA. Hasil kajian menunjukkan bahwa kondisi broken home memberikan dampak terhadap penurunan fokus perhatian, meningkatnya tekanan emosional, dan tingginya beban kognitif siswa selama proses pembelajaran literasi dan numerasi. Selain itu, siswa cenderung mengalami kesulitan dalam mempertahankan perhatian berkelanjutan akibat tekanan psikologis yang berasal dari lingkungan keluarga. Penelitian ini menunjukkan pentingnya dukungan emosional, strategi pembelajaran yang adaptif, dan pendekatan humanis dari guru untuk membantu siswa dengan kondisi broken home.